Alur Pengurusan Keagenan Muatan Khusus Ternak Sapi MV Gloucester Express pada PT. Bahari Eka Nusantara Cabang Belawan - Dwi Sandy Prayuda; Suparman Suparman; Dina Rispianti (Jurnal Transformasi Bisnis Digital, 2026)
This study aims to analyze in-depth the process of handling special livestock cargo agency for cattle on the MV Gloucester Express ship, as well as to identify the efforts and coordination carried out with relevant agencies to ensure the efficiency and effectiveness of services while the ship is in the unloading port. The research method used is descriptive qualitative. Data was collected through field research with participatory observation techniques during the fieldwork period at PT. Bahari Eka Nusantara, supported by library research to strengthen the theoretical foundation regarding ship agency management and special cargo regulations. The research findings show that the process of handling special livestock cargo agency at PT. Bahari Eka Nusantara is well-structured, involving the preparation of detailed supporting documents, starting from the ship's arrival report to its departure. The efficiency of the service heavily relies on tight coordination with port authorities (KSOP and Animal Quarantine) and compliance with applicable technical policies. However, technical obstacles were found, such as the unpreparedness of cargo documents from the shipper and coordination issues during docking. Improvement efforts are being made through enhanced digital communication and accelerated document validation before the ship's arrival to minimize waiting time at the port.